Analysis of the influence of green intellectual capital on the sustainable performance advantage of catering SMEs in Batam city - Yulfiswandi, Yulfiswandi; Alvin, Alvin (Jurnal Ekonomi, 2024)
Over the course of time, the enterprise as a social institution, not only plays a role in promoting economic development, but also has a certain negative impact on the ecological environment and has an indispensable responsibility for the sustainable development of resources and the environment. If an enterprise fulfills its social responsibilities, and through technological innovation, it can not only reduce energy consumption, but also save resources, reduce enterprise production costs, and thereby enhance enterprise competitiveness. Moreover, the global challenges from COVID-19 directly impacted 82.9% of small, medium, and micro businesses. Therefore, this study will examine the impact of Sustainability Performance to increase product competitiveness. by using 3 aspects that influence Sustainability Performance, namely Green Human Capital, Green Structural Capital, and Green Relational Capital.